Expressions of VGLUT1/2 in the inspiratory interneurons and GAD65/67 in the inspiratory Renshaw cells in the neonatal rat upper thoracic spinal cord. (December 2018) - Iizuka, Makito; Ikeda, Keiko; Onimaru, Hiroshi; Izumizaki, Masahiko
Highlights: About half of the inspiratory interneurons in the ventromedial area of the third thoracic segment are glutamatergic. These glutamatergic interneurons may enhance the inspiratory intercostal motor activity. Inspiratory Renshaw cells exist in the ventromedial area of the third thoracic segments. Most of these Renshaw cells are GABAergic, and cause a single spike followed by ventral root stimulation at neonatal stage. Abstract: Although the inspiratory spinal interneurons are thought to provide a major fraction of the excitatory synaptic potentials to the inspiratory intercostal motoneurons, this has not been confirmed. To clarify whether some inspiratory spinal interneurons are glutamatergic, we obtained whole-cell recordings from the ventromedial area of the third thoracic segments in an isolated brainstem-spinal cord preparation from neonatal rat, and the recorded cells were filled with Lucifer Yellow for later visualization. We then examined the existence of mRNA of vesicular glutamate transporters 1 and/or 2 (VGLUT1/2) by performing in situ hybridization. To discriminate the interneurons from motoneurons, we electrically stimulated the third thoracic ventral root on the recorded side, and the results verified that the antidromic spike or excitatory postsynaptic potential was not evoked. In cases in which the ventral root stimulation evoked depolarizing postsynaptic potentials, we examined the existence of glutamic acid decarboxylase 65 and/or 67 (GAD65/67) mRNA using a mixed probe to verify whether the cell was truly a Renshaw cell. The long diameter of the recorded interneurons was 22 ± 8 μm; the short diameter was 13 ± 4 μm. The interneurons' input resistance was 598 ± 274 MΩ. The Renshaw cells had similar sizes and input resistance. Six of 11 interneurons expressed VGLUT1/2, and four of five Renshaw cells expressed GAD65/67. Our findings suggest that approximately one-half of the inspiratory interneurons in the ventromedial area of the neonatal rat thoracic spinal cord are glutamatergic, and these interneurons might enhance the inspiratory intercostal motor activity.